Designed assembly of Ni/MAX (Ti3AlC2) and porous graphene-based asymmetric electrodes for capacitive deionization of multivalent ions. (March 2021) - Bharath, G.; Hai, Abdul; Rambabu, K.; Pazhanivel, T.; Hasan, Shadi W.; Banat, Fawzi
Abstract: The contamination of aquatic ecosystems by fluoride and heavy metal ions constitute an environmental hazard and has been proven to be harmful to human health. This study explores the feasibility of using asymmetric capacitive deionization (CDI) electrodes to remove such toxic ions from wastewater. An asymmetric CDI cell was fabricated using 2D Ni/MAX as an anode and 3D porous reduced graphene oxide (pRGO) as a cathode for the electrosorption of F −, Pb 2+, and As(III) ions. A simple microwave process was used for the synthesis of Ni/MAX composite using fish sperm DNA (f-DNA) as a cross-linker between MAX nanosheets (NSs) and the metallic Ni nanoparticles (NPs). Further, pRGO anode was prepared through effective reduction of RGO using lemon juice as green reducing agent with the assist of f-DNA as a structure-directing agent for the formation of 3D network. With this tailored nanoarchitecture, pRGO and Ni/MAX electrodes exhibited a high specific capacitance of 760 and 385 F g −1, respectively. The fabricated Ni/MAX and pRGO based CDI system demonstrated a high electrosorption capacity of 68, 76, and 51 mg g −1 for the monovalent F −, divalent Pb 2+, and trivalent As(III) ions at 1.4 V in neutral pH. Furthermore, Ni/MAX//pRGO system was successfully applied for the removal of total F(T), Pb(T), and As(T) ions from real industrial wastewater and contaminated groundwater. The present findings indicate that the fabricated Ni/MAX//pRGO electrode has excellent electrochemical properties that can be exploited for the removal of anionic and cationic metal ions from aqueous solutions in a CDI based system. Graphical abstract: Image 1 Highlights: The Ni/MAX nanocomposite was synthesized via a simple microwave technique. The 3D porous graphene oxide (pRGO) was prepared by using lemon juice and fish-sperm DNA. 2D-Ni/MAX and 3D-pRGO were tested as asymmetric CDI electrodes for heavy metals removal. The developed electrodes exhibited electrosorption capacity of 76 mg g −1 for Pb 2+ .